Analisis Nilai Konstanta Pegas Berdasarkan Nilai Gravitasi Bumi dan Bulan Menggunakan VLab Amrita - Amila Ashabul Jannah; Adam Malik (Pendidikan Fisika, FKIP, Universitas Nahdlatul Ulama Cirebon, 2024)
This study aims to determine the relationship between mass, spring length, and spring constant using two gravity values, namely the gravity of the earth and the moon. In addition, this research was also conducted to verify the truth of Hooke's Law. The results of this study are that the relationship between the mass of an object and the length of the spring is directly proportional, then the relationship between the length of the spring and the spring constant is inversely proportional, and the relationship between the mass of the object and the spring constant is also inversely proportional. Based on the research results, it can be concluded that gravity from the Moon and Earth does not affect the relationship between spring length, object mass, and spring constant. However, the value of gravity affects the value of the spring length, spring mass, and spring constant. On the moon, the mass will feel lighter and the length of the spring will be shorter, causing the value of the spring constant to be smaller than on earth.